2022
DOI: 10.30598/barekengvol16iss4pp1241-1248
|View full text |Cite
|
Sign up to set email alerts
|

Lee-Carter Modeling for Mortality in Indonesia With a Bayesian Approach

Abstract: This study aims to model Lee-Carter mortality with a Bayesian approach, where the parameters in the model are assumed to be random variables. The data used in this study is data on mortality rates by age group from the period 1950–2015. The sourced of data was from the UN website. Age groups are categorized by age 0 years, 1-5 years, 6-10 years, 11-15 years, ..., 86-90 years. The results of this study are from Bayes estimation obtained information that the average infant mortality rate (population aged less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Several research suggested tweaks to the Lee-Carter model that would make it more effective at modeling and forecasting rates. Some examples of these adjustments are using a Bayesian method [30] incorporating randomness or an error term into the model [30], [31], or employing a state-space model to get around the biodemographic constraint and using resampling method to improve forecasting accuracy [32]. Moreover, Lee-Carter model has been contrasted with other models, including the neural networks [33], autoregressive integrated moving average (ARIMA) model [34], and modified Lee-Carter model with bias-corrected estimators [35].…”
Section: Introductionmentioning
confidence: 99%
“…Several research suggested tweaks to the Lee-Carter model that would make it more effective at modeling and forecasting rates. Some examples of these adjustments are using a Bayesian method [30] incorporating randomness or an error term into the model [30], [31], or employing a state-space model to get around the biodemographic constraint and using resampling method to improve forecasting accuracy [32]. Moreover, Lee-Carter model has been contrasted with other models, including the neural networks [33], autoregressive integrated moving average (ARIMA) model [34], and modified Lee-Carter model with bias-corrected estimators [35].…”
Section: Introductionmentioning
confidence: 99%
“…Several research suggested tweaks to the Lee-Carter model that would make it more effective at modeling and forecasting rates. Some examples of these adjustments are using a Bayesian method [26] incorporating randomness or an error term into the model [26,27], or employing a state-space model to get around the biodemographic constraint. Moreover, Lee-Carter model has been contrasted with other models, including the neural networks ( [28]), autoregressive integrated moving average (ARIMA) model ( [29]), and modified Lee-Carter model with bias-corrected estimators ( [30]).…”
Section: Introductionmentioning
confidence: 99%